Dynamic contracting for development aid projects: Mechanism design and high performance computation - Salim Rashid; Jamsheed Shorish; Nahil Sobh (Institute for Advanced Studies (IHS), 2006)
Developing economies share both microeconomic and macroeconomic characteristics which are often unique relative to their more developed counterparts. Indeed, many authors (e.g. Parente and Prescott 2000) have emphasized the role of institutional frictions within developing nations as a major determinant of economic growth (or the lack thereof). We examine one type of institutional friction, concerning the observation and reporting of information, and construct a straightforward dynamic contracting model of foreign donor investment in an aid project. We show that even within a simple class of such models, the dynamic contracting problem rapidly becomes computationally intensive, yet remains manageable when high performance. We argue that the natural modeling, simulation and testing environment to both analyze development aid issues and help generate effective aid policy should involve-indeed, rely upon-high performance computational resources.
Keywords: G20; C63; D86; 330; development aid; dynamic contracts; computation